Language Subareas in Ethiopia Reconsidered - Zaborski, Andrzej (Lingua Posnaniensis, 2011)
Traditional terms and ideas of ‘Sprachbund’ and ‘language area’ as its best English equivalent are better than ‘revisionist’ neologisms. There is a North East African Macro-Area including languages belonging to the Afroasiatic, Nilo-Saharan and Bantu language families. There is an interesting phenomenon of resistance to influence and ‘borrowing’ in some realms in spite of ‘borrowing’ elsewhere in the same languages.